2012
DOI: 10.4293/108680812x13427982376789
|View full text |Cite
|
Sign up to set email alerts
|

Overnight Hospital Stay After Colon Surgery for Adenocarcinoma

Abstract: A fast-track perioperative procedure may achieve the same low-risk, low-morbidity results for laparoscopic colectomy patients as seen with more conventional lengths of hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…one [5] on postoperative day (POD) 3, one [13] on POD 5, one [15] on POD 7, one [14] on POD 10, one [16] 10 and 21 and two [6,20] 30 days after surgery. Telephonic consultation was used in three studies [5,6,16]: in two studies [5,16] this was done by surgeons, in one [6] by nurses.…”
Section: Discharge Criteria and Outpatient Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…one [5] on postoperative day (POD) 3, one [13] on POD 5, one [15] on POD 7, one [14] on POD 10, one [16] 10 and 21 and two [6,20] 30 days after surgery. Telephonic consultation was used in three studies [5,6,16]: in two studies [5,16] this was done by surgeons, in one [6] by nurses.…”
Section: Discharge Criteria and Outpatient Follow-upmentioning
confidence: 99%
“…Eleven studies [5,6,[12][13][14][15][16][17][18][19][20] were included in the ALC protocol discussion.…”
Section: Ambulatory Colectomy Protocolsmentioning
confidence: 99%
“…Meta‐analyses of randomized clinical trials have concluded that laparoscopic cholecystectomy with intraoperative CBD exploration and ERCP have similar rates of stone clearance, morbidity and mortality. However, when laparoscopic cholecystectomy and CBD exploration are used as a single‐stage approach, the procedure is associated with a shorter hospital stay and is likely to be more cost‐effective than ERCP with sequential cholecystectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, our comparison group from 2013 had a better than expected LOS of 4.2 days and 3.69 days for open and MIS approaches, respectively-within the 2-5 day range purported as the benefit of ERAS protocol introduction 4,5 and far below the national average of 7-10 days. 6 It is worth noting some elements of the protocol such as early ambulation, MIS approaches, and early nutrition were already informally being practiced, so it could be we were already attaining the maximal gains from beneficial portions of the protocol prior to standardization.…”
Section: Discussionmentioning
confidence: 64%